PENGARUH SUMBER INFORMASI ONLINE TERHADAP NIAT BELI MOBIL DI KOTA BANDA ACEH DENGAN VARIABEL SIKAP SEBAGAI MEDIASI - Sri Wahyuni, Teuku Meldi Kesuma (Departemen Manajemen, 2017)
This study aimed to examine the effect of online resources from electronic word-of-mouth (e-WOM), a neutral site, the manufacturer's website to purchase intention cars in Banda Aceh. This research was conducted in Banda Aceh people who use online resources to find information about the car before making a purchase. Respondents are prospective car buyers. The samples used were selected through non probability sampling with purposive sampling technique. Two hundred questionnaires were distributed to the respondents and then the data is processed using software SmartPLS 3.0. The results of this study indicate that the resources of the electronic word-of-mouth (e-WOM), neutral websites, manufacturer websites have a significant influence on consumer purchase intention. Keywords: Electronic Word-of-Mouth (e-WOM), Neutral Websites, Manufacturer Websites, Purchase Intentions